(untitled) (Studia Prawnicze / The Legal Studies, 2016)
Problematyka odpowiedzialności międzynarodowej, w odróżnieniu od innych fundamentalnych zagadnień z zakresu prawa międzynarodowego, takich jak prawo legacji czy prawo traktatów, nie została dotąd skodyfikowana w sposób wiążący. Mimo że w debatach dotyczących odpowiedzialności zarówno doktryna, jak i same podmioty prawa międzynarodowego zazwyczaj odwołują się do przygotowanego przez Komisję Prawa Międzynarodowego (KPM) projektu artykułów dotyczących odpowiedzialności państw za czyny międzynarodowo bezprawne z 2001 r., niektóre zawarte w nim koncepcje nigdy nie spotykały się z powszechną akceptacją. The aim of the article is to compare the way in which the issue of responsibility for violations related to the acts of unrecognized authorities claiming to be States is treated by the European Court of Human Rights and other international courts, particularly the International Court of Justice and the International Criminal Tribunal for the former Yugoslavia. The article considers in detail the relations between jurisdiction and responsibility, responsibility of parent States (including the concept of “positive obligations”) and responsibility of States which provide assistance to unrecognized regimes (with emphasis put on the concept of “effective control”). The results of the study indicate that the jurisprudence of the European Court differs in several important aspects from decisions of other international courts. These differences, while undoubtedly enhancing the protection of human rights in Europe, contribute to the process of fragmentation of the law of international responsibility.